2019
DOI: 10.14689/ejer.2019.83.4
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Teacher Educator: Journey of a Primary School Teacher

Abstract: After graduating from the faculties of education in Turkey, some of the teachers start working gravitate towards graduate education. Within or at the end of the process, these teachers start working as teacher educators at universities by finding positions or at least try to accomplish that. We do not have considerable knowledge of what these individuals experience in the process of transition from being a teacher to being a teacher educator. In this study, an attempt was made to examine the experiences of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…One form of education to answer this challenge is the implementation of Indonesian history subject at the high school level. History is a subject that instills knowledge [9,10], attitudes, values regarding the process of change and development of Indonesian society from the past to the present [11]. Learning history in schools needs to be carried out to build a scientific perspective with a time perspective, shared memory, and awareness of the core values of the nation to shape identity [12].…”
Section: Introductionmentioning
confidence: 99%
“…One form of education to answer this challenge is the implementation of Indonesian history subject at the high school level. History is a subject that instills knowledge [9,10], attitudes, values regarding the process of change and development of Indonesian society from the past to the present [11]. Learning history in schools needs to be carried out to build a scientific perspective with a time perspective, shared memory, and awareness of the core values of the nation to shape identity [12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies were found to have six or less, (e.g. Lowe, Bub‐Connor and Ball, 2019; Salinas et al., 2019; Sever and Ersoy, 2019). Based on the studies reviewed and the potential sensitive nature of the topics discussed, the study targeted five to eight participants, with a final total of five individuals having participated.…”
Section: Methodsmentioning
confidence: 99%
“…Lisansüstü eğitim alan öğretmenlerin çeşitli nedenlerle kariyerlerine üniversitelerde devam etmek istemeleri MEB'e bağlı okullarda lisansüstü eğitim almış öğretmenlerin görev yapmasının önünde önemli bir engeldir. Bu nedenlerin başında MEB'in ve okulların mesleki gelişimi pek de özendirmeyen örgüt kültürü vardır (Sever ve Ersoy, 2019). Nitekim öğretmenlerin profesyonel gelişimleri için aktif okul liderliği ve iyi yapılandırılmış öğrenme kültürünün okullarda benimsenmesi gerekmektedir (Desimone, 2009).…”
Section: Lisansüstü Eğitim Alma Nedenleriunclassified